ENHANCING HIGH SCHOOL STUDENTS’ COMPREHENSION OF DISCUSSION TEXT WITH GENDRE BASED APPROACH & FEEDBACK - Irsyad Nugraha; Emi Emilia; Wawan Gunawan (Indonesian EFL Journal, 2025)
The Genre-Based Approach (GBA) has been a common teaching method in Indonesia for many years, particularly for learning how to write. GBA consists of four stages: 1) Building Knowledge of the Field, 2) Modeling of the Text, 3) Joint Construction of the Text, and 4) Independent Construction of the Text. This research examines how effectively GBA and teacher feedback can improve high school students' understanding of discussion texts. This research combined Classroom Action Research (CAR) with a Genre-Based Approach (GBA) to investigate learning outcomes in a class of 12th - grade at SMA Negeri 1 Garut. The CAR cycle, involving planning, action, observation, and reflection, was interwoven with the GBA stages: building field knowledge, modeling, joint construction, and independent construction of texts. The Genre-Based Approach (GBA) provides a structured framework for analyzing texts, making it easier for both teachers and students. By breaking down the structure of texts like discussions, GBA helps students understand how to present their own arguments effectively, including counterarguments and reasoned conclusions. Furthermore, providing constructive feedback to students is essential for their learning. This feedback not only improves their understanding of the material but also enhances their interest, motivation, and performance in future assignments.The study found that GBA is beneficial for improving students' understanding of discussion texts. However, the research also highlighted that the successful implementation of GBA often depends on the teacher providing effective feedback to students. The study concluded that when implemented effectively, GBA, combined with constructive teacher feedback, significantly enhances high school students' writing skills for discussion texts.Keywords: Genre-based Approach (GBA); feedback; high school; writing skill; discussion text